MEDICINAL SIGNIFICANCE OF NOVEL COUMARINS: A REVIEW - PATIL, SHARANABASAPPA B.; P., GOURAMMA; JALDE, SHIVAKUMAR S. (International Journal of Current Pharmaceutical Research, 2021)
Coumarone is a chemical compound found in many plants. Coumarone having diverse pharmacological properties popularly known as an antimicrobial, Analgesic anti-inflammatory, Anticancer, Antiviral, anticoagulant, antihypertensive, anticonvulsant, antihyperglycemic, antioxidant, activities. Coumarone was also observed in all green color veggies, and also in fruits and their seeds, dark coffee, tea leafs, further it is used for herbal remedies due to having less toxicity, very cheaper. The most useful method for the synthesis of Coumarone is from phenol and ethyl acetate and also by using catalyst. In this paper we tried to update the observations of authors towards the biological and medicinal significance of novel the natural and synthetic coumarone derivatives.